Increased cesarean section rate in Central Saudi Arabia: a change in practice or different maternal characteristics - Al-Kadri HM; Al-Anazi SA; Tamim HM (Dove Medical Press, 2015)
Hanan M Al-Kadri,1 Sultana A Al-Anazi,1 Hani M Tamim21Department of Obstetrics and Gynecology, King Abdulaziz Medical City, 2College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Kingdom of Saudi ArabiaBackground: Cesarean section (CS) rate has shown creepy increase. We aimed in this work to identify factors contributing to increasing rate of CS in central Saudi Arabia.Methods: A retrospective cohort study was conducted at King Abdulaziz Medical City. Two groups of women were included (G1 and G2). G1 had delivered by CS during the year 2002 (CS rate 12%), and G2 had delivered by CS during the year 2009 (CS rate 20%). We compared the included women’s characteristics, neonates, CS indications, and complications. Data were analyzed using SPSS version 15 program. Odds ratios and confidence intervals were calculated to report precision of categorical data results. A P-value of ≤0.05 was considered significant.Results: A total of 198 women were included in G1 and 200 in G2. Both groups had comparable maternal and fetal characteristics; however, absence of antenatal care has resulted in 70% increase in CS deliveries for G2, P=0.008, OR =0.30, CI 0.12–0.76. Previous vaginal surgeries have contributed to tenfold increase in CS deliveries for G2, P=0.006, OR =10.37, CI 1.32–81.78. G2 had eight times increased CS deliveries than G1 due to intrauterine growth restriction, P=0.02, OR =8.21, CI 1.02–66.25, and 80% increased risk of CS was based on maternal demand, P=0.02, OR =0.20, CI 0.02–1.71. Decision taken by less-experienced staff was associated with 2.5-fold increase in CS deliveries for G2, P=0.002, OR =2.62, CI 1.39–4.93. There was a significant increase in CS deliveries under regional analgesia and shorter duration of hospital stay for G2, P=0.0001 and P=0.001, respectively. G2 women had 2.75-fold increase in neonatal intensive care unit admission, P=0.03, OR =2.75, CI 1.06–7.15.Conclusion: CS delivery rate significantly increased within the studied population. The increased rate of CS may be related to a change in physician’s practice rather than a change in maternal characteristics, and it appears to be reducible.Keywords: cesarean section, maternal morbidity, neonatal morbidity, cesarean section rate